Teaching Incision and Drainage of Abscess - Megan Freeman; Patricia Wathen; Justin Williams; Maggie Zhang (Association of American Medical Colleges, 2014)
Abstract Introduction This module provides instruction on how to teach the incision and drainage of the cutaneous abscess. It is best intended for application in small groups and can be applied in interdisciplinary team-based learner settings. Methods This teaching module utilizes simulation techniques to improve learner competence. It is designed to allow the instructor to create a simulation-based curriculum for learners at any level of training for teaching incision and drainage of the cutaneous abscess. It provides instruction on making low-cost simulated models as well as tools and tips for implementation of the course. Additionally, this module provides the instructor with pre- and posttesting tools, a procedure checklist, and tools for teaching informed consent. The module takes about 90 minutes to complete. Results The pre- and posttests for this module were given to third-year medical students, who demonstrated a significant improvement in their ability to list the equipment needed and the essential steps of the procedure. Most learners also felt that it was a valuable learning experience that should be provided to all third-year medical students. Discussion Benefits of this model of teaching incision and drainage of abscesses include little expense of materials (approximately $1.00 per abscess) and minimal odor due to the use of toothpaste as "pus."